STUDY OF THE SLEEP MOTIVE IN AZERBAIJANI PHILOLOGY - Rasulova , Tansu (Collection of scientific papers «ΛΌГOΣ», 2022)
Sleep is the object of various areas of research in natural sciences and humanities. In fiction, special attention is paid to dreams as a method of revealing the personality of a character.